EPID-21. PREDIAGNOSTIC PRESENTATIONS OF GLIOMA IN PRIMARY CARE: A CASE-CONTROL STUDY. (5th November 2018) - Peeters, Marthe; Dirven, Linda; de Waal, Margot; Numans, Mattijs; Taphoorn, Martin
Abstract: BACKGROUND: Little is known about symptoms and signs of glioma patients in the year(s) before diagnosis. This study aimed to assess the prevalence of clinical symptoms glioma patients may present with to the general practitioner (GP) in the five years prior to diagnosis, and whether these can be distinguished from patients with (1) other central nervous system (CNS) disorders or (2) any other condition. METHODS: Glioma patients were matched to controls based on age, sex and diagnosis date, using anonymized GP registries. Prevalences of nine prediagnostic symptoms (seizures, headaches, motor impairments, cognitive/mental impairments, visual disorders, mood disorders/fear, general symptoms, sensory complaints and metabolic/endocrine symptoms) were evaluated in the five years prior to diagnosis, and divided into three time periods: 60-24 months, 24–6 months and ‹6 months. RESULT: Thirty-six glioma patients were matched with 72 control patients. In total, 2491 (range 0–102) visits to the GP were analyzed. There were no significant differences between groups in the number of visits over 5 years (711 versus 989 versus 791 in glioma, CNS and other patients respectively; p=0.381), or in each of the three time periods (data not shown). The prevalence of motor symptoms in the period 60-24 months was significantly higher in the CNS patients as opposed to the other groups (4 versus 0 in both groups; both p=0.039). Moreover, ‹6 months prior to diagnosis CNS patients differed significantly in mood disorders/fear compared to other controls (8 versus 0, p=0.012), but not glioma patients versus CNS patients (5 versus 8, p=0.816) or glioma versus other patients (p=0.221). CONCLUSION: In this sample, glioma patients could not be distinguished from CNS or 'other' control patients with respect to the number of GP visits before diagnosis or prediagnostic symptoms. Nevertheless, when mood disorders occur, all CNS disorders should be considered by the GP, including glioma.